Inside Cover: Domino Reaction Catalyzed by Zeolites with Brønsted and Lewis Acid Sites for the Production of γ‐Valerolactone from Furfural (Angew. Chem. Int. Ed. 31/2013). Issue 31 (19th July 2013) - Bui, Linh; Luo, Helen; Gunther, William R.; Román‐Leshkov, Yuriy
<x xml:space="preserve">Abstract</x> The selective conversion of furfural into γ‐valerolactone (GVL) through a series of domino‐like reactions catalyzed by zeolites with Lewis and Brønsted acid sites is described by Y. Román‐Leshkov and co‐workers in their Communication on page 8022 ff. Zr‐Beta and Al‐MFI nanosheets generated GVL in 78 % yield without the use of high‐pressure molecular hydrogen or precious metals.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>